The association of environmental heat stress with performance: analysis of the 2014 FIFA World Cup Brazil - Nassis, G. P.; Brito, J.; Dvorak, J.; Chalabi, H.; Racinais, S. (British Journal of Sports Medicine, 2015)
Objective: The 2014 FIFA World Cup Brazil included 64 matches in temperate to tropical environmental conditions. We analysed performance data in relation to the environmental conditions to identify potential association. Methods: Wet-bulb globe temperature (WBGT) parameters were obtained at the centre of the field 1 h before the start of play. Environmental stress was estimated (low, moderate and high) for each match using WBGT and relative humidity. Various physical and technical performance indices were recorded during each match (average of both teams). Results: Over the 64 matches, 28 were played under low, 20 under moderate and 16 under high environmental stress. There was no difference in actual playing time (p=0.517), total distance covered (p=0.491), number of goals scored (p=0.485) and number of cards (p=0.618) between the matches played under different environmental stress categories. The number of sprints was lower in high than in moderate or low environmental stress (-10%, p<0.05) but peak speed was unaffected. The distance covered at high intensity was also lower under high (24.8±2.8 m/min/player) than low environmental stress (26.9±2.3 m/min/player, p=0.02). Number of passes was not different but the rate of successful passes was higher under high (76.8±4.4%) than low (73.6±10.8%) environmental stress (p=0.031). Conclusions: Top-level players seem to modulate their activity pattern during matches in a hot and humid environment (ie, less high-intensity but more low-intensity running and successful passes) to preserve the global match characteristics (ie, similar actual playing time, total distance covered, peak running speed and goals scored).